2017
DOI: 10.3390/su9040580
|View full text |Cite
|
Sign up to set email alerts
|

A World without Hunger: Organic or GM Crops?

Abstract: It has been estimated that the world population will increase to 9.2 billion by 2050; supplying the growing population with food will require a significant increase in agricultural production. A number of agricultural and ecological scientists believe that a large-scale shift to organic farming (OF) would not only increase the world's food supply, but might be the only way to eradicate hunger sustainably. Nevertheless, OF has recently come under new scrutiny, not just from critics who fear that a large-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 69 publications
(108 reference statements)
1
15
0
11
Order By: Relevance
“…Global commercial cultivation of GM crops has reached to an aggregate land mass of two billion hectares over the last two decades, with total generated benefits of 150.3 billion US$ (Brooks and Barfoot, 2016). The so-called 20 th anniversary of GM crops resulted in significant net economic benefits (through yield and production gains as well as from cost savings) ultimately reducing yield gaps, reduced pesticide application, and conservation of zero tillage (Brookes and Barfoot, 2016;Taheri et al 2017). However, although cultivation of GM crops and their use in food and feed has not delivered what was expected in terms of accomplishment and GM technology has attracted an ever-increasing and an extremely emotional and complex scientific and political debate, involving a very wide community of different groups ranging from environmental conservationists and ecologists, to evolutionary M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Global commercial cultivation of GM crops has reached to an aggregate land mass of two billion hectares over the last two decades, with total generated benefits of 150.3 billion US$ (Brooks and Barfoot, 2016). The so-called 20 th anniversary of GM crops resulted in significant net economic benefits (through yield and production gains as well as from cost savings) ultimately reducing yield gaps, reduced pesticide application, and conservation of zero tillage (Brookes and Barfoot, 2016;Taheri et al 2017). However, although cultivation of GM crops and their use in food and feed has not delivered what was expected in terms of accomplishment and GM technology has attracted an ever-increasing and an extremely emotional and complex scientific and political debate, involving a very wide community of different groups ranging from environmental conservationists and ecologists, to evolutionary M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnology can also help conduct organic food production. Thus, organic farming can be achieved with the use of biotechnological tools (Dubey, 2014;Cano et al, 2017;Taheri et al, 2017). In this regard pest management (Brzozowski and Mazourek, 2018), durable molecular breeding (Gheysen and Custers, 2017) are also useful for organic farming.…”
Section: Contribution Of Biotech Crops To Sustainable Developmentmentioning
confidence: 99%
“…Another research group in Japan found that compared to single introduction of individual genes, introduction of multiple iron homeostasis genes is more effective for iron biofortification (Masuda et al, ). However, widespread skepticism about transgenic food limits the promotion of transgenic high‐iron rice worldwide (Davidsson, ; Lee & Krimsky, ; Taheri, Azadi, & D’Haese, ).…”
Section: Ways To Improve Low Iron Levelsmentioning
confidence: 99%